199k views
1 vote
11 What is the solution to the equation 3(x - 4) = 2(x - 6)?

A x = 0
B X = 1
C
There are infinitely many solutions.
D There is no solution.
Uw did hot that anawe

User John Lyon
by
5.6k points

1 Answer

6 votes

Start by distributing through the parentheses on

each side of the equation to get 3x - 12 = 2x - 12.

Now move your x's to the left by subtracting

2x from both sides to get x - 12 = - 12.

Now move your numbers to the right by

adding 12 to both sides to get x = 0.

So, the solution to this equation is x = 0.

User Nguyenkha
by
4.7k points